Perlindungan Hukum terhadap Karya Kecerdasan Buatan (AI): Tantangan dan Peluang bagi Sistem HAKI Indonesia: Penelitian - Urbanisasi; Agusman (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Rapid advances in the field of artificial intelligence (AI) have resulted in a variety of original works covering various creative fields, such as images, music, design, and scientific content. However, this raises a fundamental question in Indonesia's intellectual property rights (IPR) system, namely who should own the rights to works produced by AI, should the rights belong to the AI machine itself, the developers of the technology, or the users who utilize AI in the creative process? This study aims to conduct an in-depth analysis of the IPR legal framework in Indonesia in terms of protection for AI-based works, while also examining various challenges, both normative and practical, that arise in this context. The research method applied is juridical-normative with an approach that involves a review of applicable laws and regulations, relevant legal concepts, and comparisons with regulations and legal practices in several countries that have already regulated works produced by AI. The results of this study reveal that positive law in Indonesia currently does not explicitly regulate the ownership and protection of intellectual property rights for works produced by AI. This situation has the potential to create a normative vacuum and legal uncertainty that could have various negative implications for innovators and the creative industry. On the other hand, there are various opportunities to update regulations to accommodate developments in digital innovation, including establishing a new concept of authorship, strengthening the moral and economic rights of creators, and developing a protection scheme that is more adaptive to ever-evolving technological advances. Based on these findings, this study recommends the need to establish specific regulations or revise existing IPR laws to ensure legal certainty, provide fair protection for relevant parties, and support the sustainable development of AI technology in Indonesia.